你可能感兴趣的试题
x2+6xy+9y2=(x+3y)2 2x2﹣4xy+9y2=(2x﹣3y)2 2x2﹣8y2=2(x+4y)(x﹣4y) x(x﹣y)+y(y﹣x)=(x﹣y)(x+y)
12abc-9a2b2=3abc(4-3ab) 3x2y-3xy+6y=3y(x2-x+2y) -a2+ab-ac=-a(a-b+c) x2y+5xy-y=y(x2+5x)
xy(2x-2y)2 2xy(x-y)2 4xy(x2-2xy+y2) 4xy(x-y)2
12abc-9a2b2c=3abc(4-3ab) 3x2y-3xy+6y=3y(x2-x+2y) -a2+ab-ac=-a(a-b+c) x2y+5xy+y=y(x2+5x+1)
a2b+7ab-b=b(a2+7a) 3x2y-3xy+6y=3y(x2-x+2) 8xyz-6x2y2=2xyz(4-3xy) -2a2+4ab-6ac=-2a(a-2b-3c)
3x2-6x=x(3x-6) -a2+b2=(b+a)(b-a) 4x2-y2=(4x+y)(4x-y) 4x2-2xy+y2=(2x-y)2
8x2y-24xy2=8xy(x-3y); ax+bx+ay+by=x(a+b)+y(a+b) 12x2y+14x2y2-2xy=2xy(6x+7xy-1); x3-8=(x-2)(x2+2x+4)
12abc-9a2b2=3abc(4-3ab) 3x2y-3xy+6y=3y(x2-x+2y) -a2+ab-ac=-a(a-b+c) x2y+5xy-y=y(x2+5x)